Improving the Dispersity of Nano-silica from Rice Hull Ash in Organic Solvents by a New Surface Modification Method - Li, Yulin (Asian Journal of Chemistry, 2012)
Different surface modification methods improving the dispersity of nano-silica from rice hull ash in organic solvents by g-methacryloxypropyltrimethoxy silane in anhydrous alcohol solution were investigated. The optimum modification method was that nano-silica powders were chemically modified by g-methacryloxypropyltrimethoxy silane in anhydrous alcohol solution and g-methacryloxypropyltrimethoxy silane in anhydrous alcohol solution was dropwise added at 3 mL/min. Dibutyl phthalate absorption number of the optimum modified nano-silica was 3.2 cm3/g.